PENGGUNAAN BUDAYA POPULER DALAM DIPLOMASI BUDAYA JEPANG MELALUI WORLD COSPLAY SUMMIT - Wardana, I Made Wisnu Saputera; Fasisaka, Idin; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT Nowadays, every country in order to fulfill their national interest, they will not only focused on their military or economic power but also their cultural influence. The cultural aspect is viewed as one of power sources that have great influence. Japan is one of the countries that regularly do cultural diplomacy. Japan believes that cultural approachment could build a good relations between Japanand other countries. Recently,Japan’s cultural diplomacy tend to use it’s pop-culture such as manga, anime, fashion, cosplay or Japan’s popular music. One of Japan’s cultural diplomacy activities that using Japan’s popular culture is World Cosplay Summit (WCS). This research aimed to described Japan’s cultural diplomacy activity that using Japan’s popular culture to strengthened Japan’s positive image through WCS event that held in Nagoya in the year of 2003-2014 with refer to elements from soft power currencies concept. Keywords : Cultural Diplomacy, Soft Power Currencies, WCS, Japan